Benefits of Dexmedetomidine in Management of Post-ECT Agitation. Issue 3 (September 2017) - Narang, Puneet; Ianovich, Francesca; Sarai, Simrat Kaur; Lippmann, Steven
Abstract : Abstract: Electroconvulsive therapy (ECT) is an intervention for patients with a variety of psychiatric conditions. Occasionally, people exhibit dangerous degrees of agitation after this treatment, and some do not respond well to conventional pharmacotherapies. Dexmedetomidine is a central α-2 agonist that can induce significantly calmative effects in persons with post-ECT agitation. The indication for it is in calming individuals with acute and/or recurrent posttreatment agitation. Dexmedetomidine is safe and effective when infused just before, or postictally, at ECT sessions.